2015
DOI: 10.17221/8533-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Changes in leukocyte counts, lymphocyte subpopulations and the mRNA expression of selected cytokines in the peripheral blood of dogs with atopic dermatitis

Abstract: Canine atopic dermatitis (CAD) is a chronic allergic disease characterised by genetic predisposition. The exact pathogenesis of the disease is still not fully understood. Blood parameters, lymphocyte subpopulations, cytokines and other molecules involved in pro-and anti-inflammatory activities, and Th1/Th2 polarisation in peripheral blood were assessed in clinically healthy dogs and dogs with AD by haematological examination, flow cytometry and qRT-PCR. The group of diseased dogs was further divided into subgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…By contrast, a more recent study could not detect any difference in plasma IL‐10 and TFG‐β concentration between atopic and healthy dogs 41 . Some studies in canine experimental AD or client‐owned dogs even showed an upregulation of IL‐10 or TGF‐β mRNA in the PBMCs or lesional skin samples 12,21,90 . One could infer that this upregulation of immunosuppressive cytokines is merely a normal compensatory response to control skin inflammation and is not specific to AD.…”
Section: Updates On Cytokines and Chemokines In Canine Atopic Dermatitismentioning
confidence: 89%
See 3 more Smart Citations
“…By contrast, a more recent study could not detect any difference in plasma IL‐10 and TFG‐β concentration between atopic and healthy dogs 41 . Some studies in canine experimental AD or client‐owned dogs even showed an upregulation of IL‐10 or TGF‐β mRNA in the PBMCs or lesional skin samples 12,21,90 . One could infer that this upregulation of immunosuppressive cytokines is merely a normal compensatory response to control skin inflammation and is not specific to AD.…”
Section: Updates On Cytokines and Chemokines In Canine Atopic Dermatitismentioning
confidence: 89%
“…37 Of the remaining studies, four showed no difference, and one showed reduced, although not significantly, protein and mRNA levels of IFNγ in the blood (sera, plasma and PBMCs). [38][39][40][41]90 The mRNA expression of IFNγ also was unchanged after HDM challenge in the acute skin lesions or primary keratinocytes collected from the cAD model, 21,91 whereas its mRNA expression was significantly increased in PBMCs collected from dogs of a similar AD model. 12 A study of dogs treated with oclacitinib showed that IFNγ production by peripheral blood CD4 + and CD8 + T cells was significantly reduced on Day (D)240 and D300 after the initiation of treatment yet returned to baseline levels on D360 without an associated clinical relapse.…”
Section: Interferonγmentioning
confidence: 98%
See 2 more Smart Citations
“…Lebih lanjut diungkapkan bahwa jumlah eosinofil absolut yang ditemukan berkorelasi positif dengan rasio neutrofil terhadap limfosit (NLR) pada anjing dermatitis. Sedangkan, Hoskova et al (2015) melaporkan, anjing yang menderita Canine atopic dermatitis (CAD) menunjukkan neutrofilia ringan tanpa leukositosis umum, dengan penurunan jumlah limfosit absolut. Profil ini dapat digunakan untuk diagnostik dalam mengukur respons inflamasi yang dapat dipakai dalam membantu pengobatan (Ambily et al, 2022).…”
Section: Total Leukosit Anjing Dermatitis Dan Non-dermatitisunclassified